2016
DOI: 10.1002/ptr.5627
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of UDP-Glucuronosyltransferase (UGT) Isoforms by Arctiin and Arctigenin

Abstract: Arctiin is the major pharmacological ingredient of Fructus Arctii, and arctigenin is the metabolite of arctiin formed via the catalysis of human intestinal bacteria. The present study aims to investigate the inhibition profile of arctiin and arctigenin on important phase II drug-metabolizing enzymes UDP-glucuronosyltransferases (UGTs), indicating the possible herb-drug interaction. In vitro screening experiment showed that 100 μM of arctiin and arctigenin inhibited the activity of UGT1A3, 1A9, 2B7, and 2B15. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…In our experiments, it was found that MGF and NTR activated UGT 1A10 and deglycosylation of MGF into NTR strongly increased the inhibitory effects towards others tested UGT isoforms except UGT1A10. The deglycosylation of saponin to aglycone always exhibited a different inhibition profile, such as astragaloside IV and cycloastragenol, glucoaurantio-obtusin and aurantio-obtusin, liquiritin and liquiritigenin, icariin and its intestinal metabolites (icariside I, icariside II and icaritin), arctiin and arctigenin, scutellarin and scutellarein, and in most situations, aglycone showed stronger inhibitory effects than saponin [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. In our study, in silico docking method was used to explain why the inhibition potential of NTR was stronger than MGF on the activity of UGT1A3, UGT1A7 and UGT1A9.…”
Section: Discussionmentioning
confidence: 99%
“…In our experiments, it was found that MGF and NTR activated UGT 1A10 and deglycosylation of MGF into NTR strongly increased the inhibitory effects towards others tested UGT isoforms except UGT1A10. The deglycosylation of saponin to aglycone always exhibited a different inhibition profile, such as astragaloside IV and cycloastragenol, glucoaurantio-obtusin and aurantio-obtusin, liquiritin and liquiritigenin, icariin and its intestinal metabolites (icariside I, icariside II and icaritin), arctiin and arctigenin, scutellarin and scutellarein, and in most situations, aglycone showed stronger inhibitory effects than saponin [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. In our study, in silico docking method was used to explain why the inhibition potential of NTR was stronger than MGF on the activity of UGT1A3, UGT1A7 and UGT1A9.…”
Section: Discussionmentioning
confidence: 99%
“…Natural lignans from Arctii Fructus could inhibit the activity of P-gp 405 . Furthermore, Arctiin and Arctigenin showed an inhibitory effect on UGTs 406 . UGT1A9, UGT2B7, and UGT2B17 were the major isoforms responsible for the 4′- O -glucuronidation of Arctigenin in human intestine microsomes 407 .…”
Section: Tcms For the Treatment Of Covid-19 Infectionsmentioning
confidence: 93%
“…Arctigenin and arctiin have many therapeutic properties including anti-tumor and anti-inflammatory activities. 6,7) Since arctiin is metabolized into arctigenin by intestinal bacteria, 8,9) the physiological effects of arctiin in vivo may be attributed to the physiological activity of arctigenin. Arctigenin may affect the vascular endothelial cells because it has reported to suppresses tumor growth via inducing changes of vascular structure.…”
Section: Introductionmentioning
confidence: 99%